ANALYSIS OF TYPICAL CAPABILITIES AND ENTREPRENEURIAL ORIENTATION AGAINST COMPETITIVE ADVANTAGE IN BANDUNG TRADITIONAL FOODS MSMES - Ferdinandus Sampe; Andri Haryono; Daniel Lallo Pakiding; Norvadewi Norvadewi; Muhammad Yusuf (Jurnal Ekonomi, 2022)
Traditional food is food that has been consumed since the previous generation, is regional in nature, and has been adapted to the tastes of the local community. The goal of this study is to determine the impact of distinct capabilities and entrepreneurial orientation on competitive advantage in traditional Bandung food SMEs. The independent variables in this study are distinct capabilities and entrepreneurial orientation, and the dependent variable is competitive advantage. The research method used is quantitative. In this study, 32 SMEs representative of Bandung traditional food were sampled using the saturated sample technique. The researchers used multiple linear regression analysis techniques with the SPSS data processing application version 26. According to the findings of this study, there was a positive and significant relationship between typical capabilities and competitive